Impact of COVID-19 on the physical activity and quality of life of patients in cardiac rehabilitation - Delgado, Bruno (2021)
Background: COVID-19 conditioned the normal functioning of health services, requiring a restructuring in their care capacity, specifically cardiac rehabilitation units. Objectives: to evaluate the impact of the pandemic on the quality of life and level of physical activity of patients in cardiac rehabilitation program. Methodology: cross-sectional descriptive study. All patients who had to interrupt the hospital cardiac rehabilitation programme in a hospital in the north of the country were contacted by telephone, assessing their level of quality of life, using the EURO-QoL 5D questionnaire. Results: thirty-seven patients were contacted, mostly male (81%,1). The quality of life perceited is significantly reduced, and personal care is the most affected. The average quality of life index obtained is 0.850. Patients perform an insufficient level of physical activity on the basis of European recommendations. Conclusion: patients who have discontinued the cardiac rehabilitation programme have a reduced level of quality of life associated with ineffective management of their therapeutic regimen as a consequence of the pandemic.